Increasing Knowledge about Pregnancy Prevention among Adolescents through Education Intervention - Shintya, Lea Andy (Fakultas Ilmu Keperawatan Universitas Klabat, 2025)
Adolescent pregnancy has become a significant public health issue worldwide, including in Indonesia which has a negative impact on the holistic health of adolescents. One effective approach to addressing the issue of teenage pregnancy is through health education interventions aimed at increasing adolescent knowledge and awareness of reproductive health. The research aims to analyze the influence of health education on the prevention of adolescents pregnancy. The research method used was quasi-experimental with a pre-post design, involving 30 female student respondents in this study, with samples taken using the total sampling method. Data were collected by distributing questionnaires before and after the health education intervention. Data analysis was conducted using the Wilcoxon Signed Ranks Test formula. The results of the pretest and post-test scores from 30 participants. The minimum score on the pretest was 41, while the maximum score was 76, with an average of 56.90. After the treatment, the posttest scores showed a minimum of 71, a maximum of 94, with an average of 82.17. The analysis used the Wilcoxon Signed Ranks Test to see the significant difference in knowledge before and after the treatment, obtaining a p-value of 0.000 < α. 0.05. Indicates that Ho is rejected, which means that the intervention conducted has successfully increased adolescents' knowledge about pregnancy prevention among Adolescent. Further research is required to investigate other variables like video on demand or Google slide media that may affect the efficacy of interventions and to ascertain the optimal means for disseminating information to adolescents. Kehamilan remaja telah menjadi masalah kesehatan masyarakat yang signifikan di seluruh dunia, termasuk di Indonesia yang berdampak negatif pada kesehatan holistik remaja. Salah satu pendekatan yang efektif untuk mengatasi masalah kehamilan remaja adalah melalui intervensi pendidikan kesehatan yang bertujuan untuk meningkatkan pengetahuan dan kesadaran remaja tentang kesehatan reproduksi. Penelitian ini bertujuan untuk menganalisis pengaruh Pendidikan Kesehatan terhadap pencegahan kehamilan remaja. Metode penelitian yang digunakan adalah kuasi-eksperimental dengan desain pre-post, melibatkan 30 responden siswi dalam penelitian ini, dengan sampel diambil menggunakan metode total sampling. Data dikumpulkan dengan menyebarkan kuesioner sebelum dan setelah intervensi Pendidikan Kesehatan. Analisis data dilakukan menggunakan rumus Uji Wilcoxon Signed Ranks. Hasil skor pretest dan post-test dari 30 peserta. Skor minimum pada pretest adalah 41, sedangkan skor maksimum adalah 76, dengan rata-rata 56,90. Setelah perlakuan, skor posttest menunjukkan minimum 71, maksimum 94, dengan rata-rata 82,17. , Analisis menggunakan Uji Wilcoxon Signed Ranks untuk melihat perbedaan signifikan dalam pengetahuan sebelum dan setelah perlakuan, memperoleh nilai p sebesar 0.000 < α. 0.05. ,Menunjukkan bahwa Ho ditolak, yang berarti bahwa intervensi yang dilakukan telah berhasil meningkatkan pengetahuan remaja tentang pencegahan kehamilan di kalangan remaja. Penelitian lebih lanjut diperlukan untuk menyelidiki variabel lain seperti media video on demand atau google slide yang mungkin mempengaruhi efektivitas intervensi dan untuk menentukan cara terbaik dalam menyebarkan informasi kepada remaja.